Cultural Diversity And Its Role In The Creation And Evaluation Of Sustainable Development - Bouhbila, Rabah (Journal of Human Sciences, 2021)
The global transformation produced many changes at all levels where attention was how to achieve the development of society , as it is known development in the evolution of the nature of the value and significance without modern conditions and requirements , in the beginning the focus was on profit margins while in light of the growing concern for individual and regarded as a means and gool of development is the trends humanitarian development. And this has lad to ask how to keep this development under generational succession. Which very from one stage to another, hand differences displayed on the vision and cultures that produced great cultural diversity which reflects the ad valoren tool for the reorganization of society and This Is chat enhances the interaction of the cultures of the community and consider the mechanism. Of a new positive in the Field of social engineering established to activate the development at all levels until you can achieve sustainability between the generations. But this paices the problem of our study are as follows.